The pharmacokinetics and toxicity of antituberculosis agents and other co-administered drugs in children with tuberculosis, with and without HIV infection, and their relationship to nutritional status - Cilliers, Karien (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MNutr)--University of Stellenbosch, 2011.